Growth Ratio Analysis of The Baznas in The Covid-19 Pandemic - Yulia Puspitasari Gobel (Scimadly Publishing, 2023)
This study aims to calculate and analyze the growth of the ZIS Growth Ratio, Growth Of Allocation Ratio and Growth of Operational Expense Ratio in 2019, 2020 and 2021 in the Central Baznas financial reports, using Quantitative Data types in the form of numbers contained in financial reports (Collectors of funds and Distribution of Zakat funds) and analyzed using the Growth Ratio issued by the Central Baznas. Based on the results of the calculation of the ZIS Growth Ratio growth ratio, it shows that growth is not good, even in 2020 the growth ratio has decreased, but it will increase again in 2021. Furthermore, ZIS Growth Of Allocation in 2019, 2020 and 2021 shows growth that is not good but if you look at the increase every year growth has increased quite a lot, especially in 2020 of 22.33%, while the calculation results for the Growth of Operational Expense ratio have not been effective and efficient in terms of the growth rate of operational costs in managing funds used for operational activities for channeling and collecting Zakat funds, Infaq and Alms.